2017
DOI: 10.4012/dmj.2016-019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoirradiation conditions on dentin bond durability and interfacial characteristics of universal adhesives

Abstract: The influence of photoirradiation conditions on dentin bond durability and interfacial characteristics of universal adhesives was investigated. Universal adhesives were applied to the dentin surfaces and photoirradiated with 100 mW/cm for 40 s, 200 mW/cm for 20 s, and 400 mW/cm for 10 s. A resin composite was bonded to dentin to determine shear bond strength after 24 h water storage and 30,000 thermal cycles, and water contact angle of cured adhesive were measured by the sessile drop method. Greater dentin bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although universal system adhesives could maximize bonding performance to the greater extent, and optimize application procedures, there are many challenges in the clinic operations. Experiments have confirmed that steps clinical applications, such as: adhesive coating 7) , air blowing 8) , photocuring operation 9) will affect the quality of adhesive layer and significantly influence the bonding performance of universal adhesive systems 10) . It was confirmed that higher air-blowing temperature could promote the degree of solvent evaporation to achieve a better adhesive layer 10) , which contribute the durability of bonding agent as well 11) .…”
Section: Introductionmentioning
confidence: 81%
“…Although universal system adhesives could maximize bonding performance to the greater extent, and optimize application procedures, there are many challenges in the clinic operations. Experiments have confirmed that steps clinical applications, such as: adhesive coating 7) , air blowing 8) , photocuring operation 9) will affect the quality of adhesive layer and significantly influence the bonding performance of universal adhesive systems 10) . It was confirmed that higher air-blowing temperature could promote the degree of solvent evaporation to achieve a better adhesive layer 10) , which contribute the durability of bonding agent as well 11) .…”
Section: Introductionmentioning
confidence: 81%
“…in reduced concentrations compared with their precursors [6], conventional dimethacrylate cross-linkers, non-acidic emulsifying monomers, catalysts for light- or dual-curing and a proper selection of solvents to enhance monomer spreading and substrate infiltration capacity. Most studies published on these adhesives are focused on bond strength and bond durability with dental hard tissues under different testing protocols [7,8,9]. It has been shown that when universal adhesives were bonded to enamel employing the self-etch mode, lower bond strength values were obtained in comparison with the etch-and-rinse mode.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum energy density of 4000 mJ/cm 2 is required to ensure that the bond between dentin and adhesive is not affected. 23 Prettau Anterior zirconia (PAZ) aims to combine the physical properties of zirconia with high translucency to meet the aesthetic needs of anterior teeth. In previous studies, PAZ showed greater light irradiation through different thicknesses, benefiting aesthetics, and cementation, when photoactivated cements were used.…”
Section: Introductionmentioning
confidence: 99%